Evaluation of tomato genotypes (Santa Cruz type) during the Winter season, in Araguari, MG, Brazil - Peixoto, José Ricardo; Oliveira, Carlos Manoel de; Silva, Rogério Pereira da; Angelis, Bruno de; Filho, Arthur Bernardes Cecílio (Pesquisa Agropecuaria Brasileira, 1999)
A field experiment was carried out in the Jordão farm in Araguari, MG, Brazil, during the summer season, to evaluate the agronomic potential of genotypes (Santa Cruz type) of tomato. A randomized block design was used with 16 treatments (genotypes) and four replicates. The experimental plot was made up of two lines (1.00 m between lines and 0.55 m between plants) with 12 plants each (1 plant/pit). Seventeen harvests were made, starting 69 days after transplanting. Several genotypes as Saladinha, Débora Plus, SM-16 and Atlas had a good agronomic performance, being recommended to be cultivated in the region, in the summer season. Classified as AA type, the Saladinha and Atlas showed an average of 140 g/fruit. During the experiment a negative correlation, r = -0.52 and -0.54, could be observed, in the first evaluation, and correlation r = -0.55 and -0.45 in the second evaluation between total production, and commercial production in relation to geminivirus infection, respectively, for the different genotypes. The Saladinha e SM-16 hybrids showed the lowest number of infected plants, while Santa Clara Imported, Santa Clara, Jumbo AG-592 and IAC Santa Clara showed the highest number.